2010
DOI: 10.1088/0953-4075/43/13/135206
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of L-shell x-ray production cross-sections of Gd and W by low energy electron impact

Abstract: Lα, Lβ x-ray production cross-sections for Gd (Z = 64) and W (Z = 74) by electron impact up to 40 keV have been measured. Thin films with thick carbon substrates were used as targets in the experiments. The effects of multiple scattering of electrons when penetrating the target film, of electrons reflected from the thick pure carbon substrate and of bremsstrahlung photons produced by the impact of incident electrons on the target were corrected by means of Monte Carlo simulation. For Gd L-shell x-ray character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
(74 reference statements)
1
12
0
Order By: Relevance
“…Recently, many authors have reported L X-ray production cross sections for a few elements, and validation of various theoretical models are done using the data. Comparison between theory and experimental data on L-subshell production cross sections in Gadolinium (Gd, Z = 64) and Tungsten (W, Z = 74) were done by Wu et al [6]. Their experimental results on L α and L β lines agree reasonably well with DWBA theory including exchange interaction for W but deviates by 15-20% in case of Gd.…”
Section: Introductionmentioning
confidence: 85%
“…Recently, many authors have reported L X-ray production cross sections for a few elements, and validation of various theoretical models are done using the data. Comparison between theory and experimental data on L-subshell production cross sections in Gadolinium (Gd, Z = 64) and Tungsten (W, Z = 74) were done by Wu et al [6]. Their experimental results on L α and L β lines agree reasonably well with DWBA theory including exchange interaction for W but deviates by 15-20% in case of Gd.…”
Section: Introductionmentioning
confidence: 85%
“…L shell ionization cross sections are more difficult to obtain, particularly experimental data, because fluorescence yields and Coster-Kronig transition rates are poorly known; nevertheless, some analytical expressions [12,38] and theoretical approaches [40,[50][51][52] were recently developed; in addition, a number of experimental determinations of X-ray production and ionization cross sections [53][54][55][56][57][58][59] were carried out, as reviewed by Llovet et al [60].…”
Section: Characteristic X-raysmentioning
confidence: 99%
“…[11][12][13] For the reported experimental data of K-and L-shell ionization cross sections by electron impact in the incident electron energy region up to several keV, it seems that the DWBA theory is more suitable than the other recently developed theoretical models for the description of atomic ionization. [13][14][15][16][17][18] Up to now, there are very few studies for M shells. [19,20] In Ref.…”
Section: Introductionmentioning
confidence: 99%